Main oil generating macerals for coal-derived oil: A case study from the Jurassic coal-bearing Turpan Basin, NW China. (September 2017) - Chen, Jianping; Deng, Chunping; Wang, Huitong; Sun, Xuguang
Highlights: Generation potential, biomarkers and isotopes were investigated for coal macerals. Liptinite and vitrinite in mudstones generate 70% and 30% of oils respectively. Mudstone is a major source rock of oil in the Jurassic coal-bearing basins in China. Abstract: This paper examines the geochemical characteristics of pyrolysates from macerals such as the alginite, sporinite, cutinite, collotelinite and collodetrinite isolated from Jurassic coals and investigates their relative contributions to oil potential in respect to the Jurassic coal measures in the Turpan and other basins of northwest China. The alginite pyrolysate has the lightest carbon isotopic composition, followed by the sporinite and cutinite, while the collotelinite and collodetrinite pyrolysates show comparatively heavy carbon isotopic compositions. Pyrolysates from the alginite, sporinite and cutinite demonstrate much lower Pr/Ph ratios than those from the collotelinite and collodetrinite. Regarding the distributions of regular biomarkers such as steranes and hopanes, the alginite pyrolysate is comparatively rich in C27 steranes, followed by pyrolysates from the sporinite and cutinite, whereas pyrolysates from the collotelinite and collodetrinite contain little or undetectable C27 steranes. Furthermore, the pyrolysates from different kinds of macerals have remarkably different gammacerane concentrations. The gammacerane concentrations in pyrolysates from the alginite and cutinite are higher than that from the sporinite, though these macerals were separated from the same coal, whereas the collotelinite and collodetrinite pyrolysates have almost no gammacerane. The experimental results suggest that liptinite content in one given coal (e.g. alginite, sporinite and cutinite) controls the biomarker distributions in the coal-derived oils. Mass balance calculations of carbon isotopic compositions from the maceral pyrolysates show that the carbon isotopic composition of liquid hydrocarbons generated by organic matter in mudstone is very similar to that of most of the oils in the Jurassic coal-bearing basins of northwest China, while liquids from coal are much heavier than that of the oils. This indicates that the mudstone is likely to be the major source rocks of the oils, and coals likely to be the subordinate source rocks. Mass balance calculation based on the maceral contents and hydrocarbon-generative potential suggests that liptinites in mudstone in the Jurassic coal-measures of the Turpan Basin generate about 70% of oils, while the vitrinites produce about 30% of the oils. Therefore, the hydrogen-rich liptinites (alginite, sporinite and cutinite) are the main oil generating macerals, while vitrinites (collotelinite and collodetrinite) are secondary oil generating macerals in the Jurassic coal-bearing Turpan Basin and other Jurassic basins of northwest China.